Strengthening Capacity of Posyandu Cadre to Educate The Mothers: A Program Evaluation of Emotional Demonstration for Cadres in Bantul Regency - Annida Hanifah; Tis’a Salma Muthi’ah; Ani Sholikhah; Giva Tri Putri Guntari; Istia Husna Dzakiyyah; Siti Holivah; Ambar Swastiningrum (Faculty of Medicine, Public Health, and Nursing, Universitas Gadjah Mada, 2023)
Risk factor for child stunting in Indonesia is lower maternal education and inadequate complementary food for children aged 6-23 months. Posyandu cadres play an important role in empowering mothers through education and counseling mothers about the good practice of feeding infants and children. However, a preliminary survey shows that most mothers do not receive education and counseling from cadres in posyandu. Several factors behind that are low self-efficacy among cadres to carry out education or counseling, cadres feeling confused with educational content, and cadres feeling that many mothers are busy workers. The evaluation aims to assess the effectiveness of Emotional Demonstration for cadres in Bantul Regency using Easy Evaluation. Data were collected from 126 cadres who participated in the Emotional Demonstration program. Data collection was carried out by participatory observation, interview, and feedback form. An Easy Evaluation assessment was determined for each criterion, among others 1) Practice the roleplay according to the order of the emotional demonstration programs is Very Good 2) Apply communication skills according to the PAMM technique (Pertanyaan Terbuka; Afirmasi dan Apresiasi; Mendengarkan dan Merefleksikan; dan Menyimpulkan) is Good 3) Deliver key message is Very Good 4) Applying effective time management is Good. An assessment determined Excellent for the generic rubric of the Emotional Demonstration Program. The Emotional Demonstration program is feasible to be continued and applied to all cadres in Bantul. However, the implementation of Emotional Demonstration needs to emphasize communication skills. The results of the program evaluation will help guide public health policies to support the effectiveness of the stunting prevention program in Bantul Regency.